2017
DOI: 10.1007/s10278-017-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Computer-Aided Differential Diagnosis System to Distinguish Between Usual Interstitial Pneumonia and Non-specific Interstitial Pneumonia Using Texture- and Shape-Based Hierarchical Classifiers on HRCT Images

Abstract: A computer-aided differential diagnosis (CADD) system that distinguishes between usual interstitial pneumonia (UIP) and non-specific interstitial pneumonia (NSIP) using high-resolution computed tomography (HRCT) images was developed, and its results compared against the decision of a radiologist. Six local interstitial lung disease patterns in the images were determined, and 900 typical regions of interest were marked by an experienced radiologist. A support vector machine classifier was used to train and labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
(19 reference statements)
0
10
0
1
Order By: Relevance
“…Many studies have reported that HRCT is very important in determining the extent and severity of ILD. 23 25 The distribution and manifestation of HRCT lesions may be related to the pathological type of ILD. 23 Patterns of ILD have been characterized by a few HRCT manifestations, including ground-glass opacities, interlobular septal thickening, and grid-like, honeycomb-like lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported that HRCT is very important in determining the extent and severity of ILD. 23 25 The distribution and manifestation of HRCT lesions may be related to the pathological type of ILD. 23 Patterns of ILD have been characterized by a few HRCT manifestations, including ground-glass opacities, interlobular septal thickening, and grid-like, honeycomb-like lesions.…”
Section: Discussionmentioning
confidence: 99%
“… 23 25 The distribution and manifestation of HRCT lesions may be related to the pathological type of ILD. 23 Patterns of ILD have been characterized by a few HRCT manifestations, including ground-glass opacities, interlobular septal thickening, and grid-like, honeycomb-like lesions. 13 , 26 However, a patient may present all types of lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Depeursinge et al 7 demonstrated the wealth of a regional approach for the computed diagnosis using a geometric atlas of the lungs and regional texture features. More recently, a study from Jun et al 8 highlighted the discriminative power of a texture comparison between upper-lower, anterior-posterior and central-peripheral parts of the lung. This paper builds on this previous work with a dataset of 450 labeled cases and with 3 classes of ILDs, Usual Interstitial Pneumonia (UIP), Non-Specific Interstitial Pneumonia (NSIP) and Chronic Hypersensitivity Pneumonitis (CHP).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the development of therapeutic alternatives has brought about a new “moment” of growth, 9 moving us toward another point of change, in which the interpretation of imaging exams is no longer merely visual and tends to have a highly significant mathematical aspect in the aggregate. 10 It is still difficult to know what impact this will have on day-to-day clinical practice and patient management, given the existing therapeutic limitations, although it is not difficult to imagine that, with the development of new drugs, a more precise diagnostic analysis will allow individualized medicine to be used in the approach to patients with interstitial lung disease. The current issue of the JBP presents a pictorial essay that discusses, in a quite didactic manner, all of the certainties and inconsistencies that involve the diagnosis of usual interstitial pneumonia, the most prevalent form of idiopathic interstitial lung disease.…”
mentioning
confidence: 99%
“… 9 Caminha-se para outro ponto de mudança, no qual a interpretação dos exames de imagem deixa de ser meramente visual e tende a ter um aspecto matemático agregado altamente significativo. 10 O impacto disso na clínica diária e no manejo dos pacientes é algo ainda difícil de especular, dadas as limitações terapêuticas existentes, mas não é difícil imaginar que, com o desenvolvimento de novos fármacos, a análise diagnóstica mais fina se aproximará da medicina personalizada na abordagem ao paciente com doença intersticial pulmonar. A presente edição do JBP traz um ensaio pictórico que discute, de forma bastante didática, todas as certezas e inconsistências que envolvem o diagnóstico da pneumonia intersticial usual, a forma mais prevalente das doenças intersticiais pulmonares idiopáticas.…”
unclassified